The Effect of Eight Weeks Resistance Training with Two Doses of Crocin Consumption on Catalase and Glutathione Peroxidase in Kidney Tissue of Nandrolone Poisoned Rats - esfandiar heydari; ali hosseini; mohammad ali azarbayjani (Fasa University of Medical Sciences, 2019)
Background & Objective: The use of anabolic steroids causes damage to various tissues, including the kidneys. Aim of present study was to investigate the effect of resistance training with consumption of crocin on catalase and glutathione peroxidase in kidney tissues of nandrolone poisoned rats. Material & Method: Thirty rats selected and assigned to 6 groups 1) nandrolone, 2) nandrolone + training, 3) nandrolone + 12.5 mg/kg crocin, 4) nandrolone + 25 mg/kg crocin, 5) nandrolone + training + 12.5 mg/kg crocin, and 6) nandrolone + training + 25 mg/kg crocin. Groups 2, 5 and 6 performed resistance trainings for eight weeks and three sessions per week and groups of 3 to 6 received daily doses of crocin. To analyze the findings of the study, one-way ANOVA and Bonferron's post hoc tests were used (p≤0.05). Results: 12.5 mg/kg crocin, 25 mg/kg crocin, training + 12.5 mg/kg crocin and training + 25 mg/kg crocin have significant effect on reduction of catalase (p=0.001), training, training + 25 mg/kg crocin have significant effect on increase of glutathione peroxidase (p=0.001) also training + 25 mg/kg crocin rather than training + 12.5 mg/kg crocin has more effect on increase of glutathione peroxidase (p=0.001). Conclusion: Although resistances trainings with consumption of 25 mg/kg crocin have an interactive effect on increase of glutathione peroxidase; however, resistance training, crocin consumption and the simultaneous use of crocin and resistance training reduce catalase in the kidney tissue of nondronean poisoned rats.